Ambiguitas Peran Pengaruhnya terhadap Komitmen Organisasi - Nita Hernita (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2021)
The purpose of this research is to know the role ambiguity affects organizational commitment.The research method uses a descriptive verification approach with quantitative data types.The study population was the employees of PT.Madjatea Majalengka, amounting to 45employees with the determination of the sample using a saturated sampling technique with aLikert measurement scale (1-5). Data analysis was carried out through analysis, coefficient ofdetermination, and t test with processing using SPSS Version 21 application. The resultsshowed that role ambiguity had a negative and significant effect on organizationalcommitment.